Influence of Material Used for the Regenerator on the Properties of a Thermoacoustic Heat Pump - KRUK, Bartłomiej (Archives of Acoustics, 2013)
Research in termoacoustics began with the observation of the heat transfer between gas and solids. Using this interaction the intense sound wave could be applied to create engines and heat pumps. The most important part of thermoacoustic devices is a regenerator, where press of conversion of sound energy into thermal or vice versa takes place. In a heat pump the acoustic wave produces the temperature difference at the two ends of the regenerator. The aim of the paper is to find the influence of the material used for the construction of a regenerator on the properties of a thermoacoustic heat pump. Modern technologies allow us to create new materials with physical properties necessary to increase the temperature gradient on the heat exchangers. The aim of this paper is to create a regenerator which strongly improves the efficiency of the heat pump.